Surgical salvage therapy for malignant intrathoracic metastases from nonseminomatous germ cell cancer of testicular origin: analysis of a single-institution experience - Kesler, Kenneth A; Wilson, Jamison L; Cosgrove, Jason A; Brooks, Jo Ann; Messiha, Ahdy; Fineberg, Naomi S; Einhorn, Lawrence H; Brown, John W (The Journal of thoracic and cardiovascular surgery, 2005)
Cisplatin-based chemotherapy followed by surgical extirpation of residual benign disease represents the usual sequence of curative therapy for metastatic nonseminomatous germ cell cancer of testicular origin. Occasionally, residual disease is malignant in the form of either a persistent nonseminomatous germ cell cancer tumor or degeneration into non-germ cell cancer. We reviewed our institution's experience with patients undergoing salvage operations to remove malignant intrathoracic metastases. From 1981 through 2001, 438 patients with nonseminomatous germ cell cancer had operations to remove residual intrathoracic disease after cisplatin-based chemotherapy at Indiana University Hospital. A subset of 134 patients who underwent 186 surgical procedures to remove malignant metastases is the basis of this review. Fifty-nine patients had removal of pulmonary metastases, 49 had removal of mediastinal metastases, and 26 had removal of both pulmonary and mediastinal metastases. Surgical pathology demonstrated 84 patients with persistent nonseminomatous germ cell cancer tumors, 38 with degeneration into non-germ cell cancer, and 12 with both malignant pathologic categories. There were 4 (3.7%) operative deaths. The overall median survival was 5.6 years, with 55 (42.3%) patients alive and well after a mean follow-up of 5.1 years. Seventeen variables were analyzed by using Cox regression. Of these, older age, pulmonary metastases (vs mediastinal metastases), and 4 or more (vs 1) total intrathoracic metastases were significantly (P < or = .01) predictive of inferior long-term survival. Salvage thoracic surgery to remove malignant metastases from nonseminomatous germ cell cancer tumors of testicular origin can result in long-term survival in select patients. We identified variables that influence survival in this subset.